Collaborative Management in Accelerating The Completion of Permanent Housing for Victims of The Mount Semeru Eruption In Lumajang - Nico Valintino Wijaya; Selfi Selfi; Budi Helpiastuti; Ika Sisbintari (Eduvest - Journal of Universal Studies, 2025)
Disaster management, especially in terms of temporary and permanent housing in Indonesia, often does not go well and is slow. This is different from what happened in Lumajang Regency. Residential construction for residents affected by the Semeru eruption is progressing quickly. Even getting a student record. This research aims to find out how collaborative management is in accelerating the completion of permanent housing for victims of the Mount Semeru eruption in Sumbermujur Lumajang Village. For this reason, researchers used qualitative descriptive research methods in analyzing this management collaboration. Research data was collected from observations, interviews with related parties and data collection from mass media. The results of the research showed that the acceleration of development was due to the implementation of the New Public Management concept as expressed by Hood (1991). Apart from that, the implementation of collaborative management is also carried out by the government, especially regional heads, namely the Regent and Deputy Regent of Lumajang. Regional governments not only collaborate between governments, but also the private sector and the community. In line with this conclusion, it is recommended that other regional governments participate in implementing active collaborative communication patterns both with their staff and all disaster management parties. Starting from the central government, private sector and society. Meanwhile, the suggestion for the central government is that it is important to become Lumajang Regency as a model for residential development if a similar disaster occurs that requires relocation.